Higher HEI-2015 score is associated with reduced risk of Parkinson’s disease: a nationwide population-based study - Hu, Wenting; Liu, Hai; Zhang, Ying; Liu, Huanxian (Frontiers in Nutrition, 2025)
BackgroundRecent studies have highlighted the significant role of diet in the development of Parkinson’s disease (PD). However, research on the association between diet quality and PD in the general adult population of the United States remains limited. This study aims to assess the relationship between diet quality, measured by the Healthy Eating Index 2015 (HEI-2015) score, and the risk of PD.MethodsData for this cross-sectional analysis were obtained from the National Health and Nutrition Examination Survey (NHANES) from 2003 to 2018, which includes a nationally representative sample of US adults. Diet quality was measured using the HEI-2015 score, and weighted multivariable logistic regressions and restricted cubic splines (RCS) were applied to examine the correlation between HEI-2015 and PD. Threshold effects were computed using a two-segment linear regression model. Subgroup and sensitivity analyses, including multiple imputations, unweighted logistic regression, and exclusion of participants with HEI-2015 scores beyond 3 standard deviations (mean ± 3SD), were performed to assess the robustness of the findings.ResultsA total of 29,581 US adults were included in the analysis, with 286 participants diagnosed with PD. In the fully adjusted multivariable model, each 10-point increase in the HEI-2015 score was associated with a 17% reduction in the likelihood of PD (odds ratio (OR):0.858,95% confidence interval (CI):0.742–0.992, p = 0.039). Additionally, individuals with higher HEI-2015 scores had a 62% lower probability of developing PD compared to those with lower scores (OR:0.518, 95%CI:0.297–0.906, p = 0.021). RCS analysis revealed a nonlinear relationship between HEI-2015 scores and PD (p = 0.022). In the two-segment regression models, participants with HEI-2015 scores ≥ 55.500 had an adjusted OR of 0.957 for developing PD (95% CI: 0.916–0.999, p = 0.045). In contrast, no association was observed between HEI-2015 scores and PD in participants with scores < 55.500. Subgroup analyses indicated the association was modified by race and hyperlipidemia (P for interaction = 0.039 and 0.024, respectively). Sensitivity analyses further confirmed the robustness of this association.ConclusionHEI-2015 is negatively associated with the prevalence of PD. This suggests that modifiable lifestyle factors, particularly diet quality, may play an important role in reducing the risk of PD.